Public value analysis of urban park development : case study of Thokoza Park (Soweto) and Tsutsumani Park (Alexadra) - Mkhize, Osborne (My University, 2014)
Abstract This research focuses on establishing an explorative understanding of the efficacy of public value and social capital in the development of a community facility. The approach taken is comparative as it provides a basis for exploring the relationship communities have with a public facility and the significance of public value and social capital in the development and upkeep of the facility. The two facilities that are looked at are Thokoza Park in Soweto and Tsutsumani Park in Alexandra. Community parks vary in size and design but they all play a significant role. However, the community will only gain the benefits derived from the park if certain social attitudes are adhered to. Furthermore, communities need to be invested in their parks, have a shared sense of value for their parks, and a certain level of social capital and horizontal engagement with local government. One of the main findings is that abject poverty will halt any form of development and there is a need to constantly educate and motivate in order to get buy-in from communities. Keywords: Public Value, Social Capital, Networks, Trust, Reciprocity, and Recreational Space.
Keywords: Parks -- South Africa.